Adhesion and cohesion of epoxy-based industrial composite coatings. (15th July 2020) - Wei, Hongyu; Xia, Jun; Zhou, Wanlin; Zhou, Laishui; Hussain, Ghulam; Li, Qin; Ostrikov, Kostya (Ken)
Abstract: Epoxy is widely adopted in the coating industry because of its excellent performance, which can be applied to the surfaces of metal and non-metal structures for protection and/or decoration purposes. The strength of adhesion and cohesion is an essential prerequisite for coating, which will directly affect the performance and its applications. In the light of the mechanisms of adhesion and cohesion, state-of-the-art of technical enhancements on epoxy-based coating systems, performed over the past few years, are summarized and analyzed in this work. Considering the difference of failure modes, comparisons between the technical methods in terms of the effect in improvement, supporting mechanism, occasions of use, etc. Were compiled. It should be pointed out that research referring to the methods for improving the adhesive and cohesive strength of the applied coating mainly focused on the substrates, fillers and resins, whereas the work related to micro-scale mechanism of adhesion and cohesion, hybridizing nanoscale fillers, and compounded methods have already become a popular path for related research till the moment. Highlights: The conception of adhesion and cohesion strength and the significance of their enhancement has been explained. The adhesion strength comes from mechanical interlocking, the secondary bonding forces and chemical forces, and the interaction between the fillers and metal substrate. The adhesion and cohesion strength can be increased by surface treatments, modification of fillers and improvement on intrinsic properties of the epoxy matrix. The latest techniques in adhesion strength improvements have been studied and the eco-friendly methods are worth taking into consideration. With an explicit focus on improving adhesion and cohesion strength simultaneously, and the methods of incorporating nanoparticle into the epoxy-based coating improving the adhesion and cohesion strength are discussed in detail.